The issues of appraising “meaningful” participation and quality control in threaded discussion board - Ng, L.L. (Association for the Advancement of Computing in Education (AACE), 2010)
One of the most widely used interactive channels today is the electronic discussion board. This new medium is used as part of feedback-seeking channels. There are two unique characteristics, it does not require the physical presence of anyone and it does not require the simultaneous presence of anyone for feedback-seeking activities to occur. Educational practitioners have also begun to capitalize on these characteristics in their scheme of course assessment. In this study, the threaded electronic discussion board has been incorporated into part of the assessment activities for postgraduate courses. The study aims to investigate how this medium is utilized by the participants in achieving their learning goals as well as fulfilling the assessment requirement, via deciphering the content posted by participants in the threaded discussion board. The findings from the study reveal the need to realign assessment criteria related to aspects of “meaningful” participation and quality control.